Teks Eksposisi Siswa SMA Negeri 2 Siak Hulu Pendekatan: Systemic Functional Linguistics - Yuliawan, Tri; Shomary, Sudirman (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
This research uses the transitivity model to analyze how students express their ideas in expository text. This research is based on Halliday's Systemic Functional Grammar. The transitivity system is used as a basis for analyzing data. This research uses a qualitative descriptive method with a case study research model. Data collection is carried out by means of data formation, data reduction, drawing inferences, and analysis. Three stages were carried out to analyze the data, namely isolating the process, determining the type of process, and verifying the impact, who was involved in the process. This research applies interpretive content analysis to investigate the function of linguistic choices made in the text. There are 845 clauses in the exposition text which are used for analysis. The clauses are broken down into their constituent parts, the processes are identified, coded and categorized, and their roles are defined. This study found that among the main process types, material processes dominate speech with a total occurrence of 57.14%, while the existential process type is used minimally in speech with a total occurrence of 1,2%. This research concludes that language structures can produce hidden meanings for readers. This strengthens the assumption that language forms do not arise by chance, but rather have a communicative function.